2013
DOI: 10.1177/0146167213506467
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Movement and Fluid Social Cognition

Abstract: Rigid social categorization can lead to negative social consequences such as stereotyping and prejudice. The authors hypothesized that bodily experiences of fluidity would promote fluidity in social-categorical thinking. Across a series of experiments, fluid movements compared with nonfluid movements led to more fluid lay theories of social categories, more fluidity in social categorization, and consequences of fluid social-categorical thinking, decreased stereotype endorsement, and increased concern for socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
0
22
1
Order By: Relevance
“…Also associated with fluid arm movement are specific implications for the character dimension of justice, as revealed in someone who behaves fairly and equitably and is proportionate, even-handed, and socially responsible. The role of sensorimotor states in fluid social cognition, for instance, shows consequences for social judgment and behavior (Slepian et al, 2014). Thinking differently in one domain (e.g., fluid movement) influences how an individual responds to social targets in an unrelated domain (e.g., fluid thinking about gender), which facilitates curiosity (Ryan & Deci, 2000), and diminishes stereotype activation (Slepian et al, 2014).…”
Section: Leader Character's Reliance On the Pabcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also associated with fluid arm movement are specific implications for the character dimension of justice, as revealed in someone who behaves fairly and equitably and is proportionate, even-handed, and socially responsible. The role of sensorimotor states in fluid social cognition, for instance, shows consequences for social judgment and behavior (Slepian et al, 2014). Thinking differently in one domain (e.g., fluid movement) influences how an individual responds to social targets in an unrelated domain (e.g., fluid thinking about gender), which facilitates curiosity (Ryan & Deci, 2000), and diminishes stereotype activation (Slepian et al, 2014).…”
Section: Leader Character's Reliance On the Pabcsmentioning
confidence: 99%
“…The role of sensorimotor states in fluid social cognition, for instance, shows consequences for social judgment and behavior (Slepian et al, 2014). Thinking differently in one domain (e.g., fluid movement) influences how an individual responds to social targets in an unrelated domain (e.g., fluid thinking about gender), which facilitates curiosity (Ryan & Deci, 2000), and diminishes stereotype activation (Slepian et al, 2014). Slepian et al (2014) showed that study participants who made or observed fluid arm movements categorized faces more often as biracial, were more concerned with racial inequalities, and endorsed stereotypes less than those who made non-fluid arm movements.…”
Section: Leader Character's Reliance On the Pabcsmentioning
confidence: 99%
“…Race essentialism also has consequences for thinking flexibly about social and nonsocial categories. People who adopt less essentialist beliefs about race perceive race as more fluid and malleable (Chao, Chen, Roisman, & Hong, 2007;Mallon, 2007;No et al, 2008) and have more flexible perceptions of social category membership (Pauker & Ambady, 2009;Slepian, Weisbuch, Pauker, Bastian, & Ambady, 2014). Additionally, holding and making salient multiple racial identities (which goes against essentialist thinking) increases flexibility in cognitive processing (Gaither, Remedios, Sanchez, & Sommers, 2015).…”
Section: Potential Consequences Of Race Essentialismmentioning
confidence: 99%
“…in fact, historically, one common categorization heuristic was the one-drop rule whereby one drop of "Black blood" identified a mixed-race individual as Black, which White slave owners used to consign thousands of multiracial individuals to slavery (davis, 1991). however, in the present day, a number of higher-order social cognitive factors are known to influence racial categorization, especially as faces become more racially ambiguous (e.g., freeman & ambady, 2011;pauker, rule, & ambady, 2010;Slepian, Weisbuch, pauker, Bastian, & ambady, 2014). for example, those who identify strongly with their ethnic/racial ingroup tend to categorize more racially ambiguous faces as outgroup members (castano, yzerbyt, Bourguignon, & Seron, 2002;e.…”
Section: Categorization Of Racially Ambiguous Targetsmentioning
confidence: 99%